Compression Testing of Three Soft Lens Polymers with a Simulated Fingernail - Attridge, J.G; Weaver, D.S (Canadian Journal of Optometry, 2021)
An analysis of the mechanical properties of finished lenses utilizing compression testing identifies factors contributing to soft lens damage. Sauflon 70, Snoflex 50, and Toyo 515 PolyHEMA lenses, all of plano power and equal thicknesses were compressed within the optical zone by loads exerted by a simulated fingernail made of guitar pick material. Six lenses of each polymer were used for each of three tests. It was found that Toyo 515 PolyHEMA had a relatively lower compressive strength than the other two non-HEMA materials; that the Sauflon 70 had the least ability to recover once compressed; and that all three polymers did not appear to recover their previous compression strength after undergoing a dehydration/rehydration cycle. In the case of the Toyo 515 lenses, this last result was confirmed statistically.